Fabrication of helical microfibers from melt blown polymer blends. Issue 13 (27th April 2018) - Li, Hui; Huang, Hui; Meng, Xiaohua; Zeng, Yongchun
ABSTRACT: Helical fibers in micro/nanoscale resembling plant tendrils have been of increasing interest due to their unique characteristics. Fabrication of helical microfibers from polymer blends using melt blowing technique is reported in this study. An elastomeric and a stiff polymer are chosen as the raw materials, and a designed swirl‐die melt‐blowing device is used to prepare the microfibrous nonwovens. Focusing on the interfacial interaction between the polymer components induced by the polymer structure and intrinsic properties, airflow field characteristics, and processing parameters, we explore the effects of various parameters on helical fiber formation. Differential scanning calorimeter is employed to examine the rigidity of polymer chains, and the three‐dimensional airflow field simulation is carried out to reveal the airflow field characteristics. This work can provide a promising technique for producing stretchable microfibrous materials which have potential applications in field such as filtration materials and oil sorbents. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 970–977 Abstract : Microfibers with 3D spiral shapes resembling plant tendrils were fabricated by melt blowing polypropylene (PP)/polyurethane (TPU) blends. The key innovation point applied in this study is to produce microfibrous nonwovens with helical fiber morphology via melt blowing technique.